2009
DOI: 10.1021/bi901839d
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecificity of Binding of γ-Secretase Modulators to the Amyloid Precursor Protein

Abstract: Evidence has been presented (Kukar et al. 2008 Nature 453, 925-929) that certain γ-secretase modulators (GSMs) target the 99 residue C-terminal domain (C99) of the amyloid precursor protein, a substrate of γ-secretase, but not the protease complex itself. Here, NMR results demonstrate a lack of specific binding of these GSMs to monodisperse C99 in LMPG micelles. In addition, results indicate that C99 was likely to have been aggregated in some of the key experiments of the previous work, and that binding of GSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
62
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 23 publications
(48 reference statements)
8
62
2
Order By: Relevance
“…In this respect, the effects of 20 μM indomethacin and 2.5 μM sulindac sulfide can be directly compared to GxxxG mutants G29A and G33A (5,7). From previous NMR measurements with purified and monodisperse C99 in lyso-myristoylphosphatidylglycerol micelles, the authors have concluded that interactions with sulindac sulfide are of nonspecific nature (15), which is seemingly in contradiction with our results obtained from the ToxR assay. Here, in a natural lipid bilayer, Aβ42-lowering compounds affected APP-TMS dimerization, although we cannot specify whether existing dimers are disrupted or if binding to monomers inhibits the reassociation and the dimer formation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this respect, the effects of 20 μM indomethacin and 2.5 μM sulindac sulfide can be directly compared to GxxxG mutants G29A and G33A (5,7). From previous NMR measurements with purified and monodisperse C99 in lyso-myristoylphosphatidylglycerol micelles, the authors have concluded that interactions with sulindac sulfide are of nonspecific nature (15), which is seemingly in contradiction with our results obtained from the ToxR assay. Here, in a natural lipid bilayer, Aβ42-lowering compounds affected APP-TMS dimerization, although we cannot specify whether existing dimers are disrupted or if binding to monomers inhibits the reassociation and the dimer formation.…”
Section: Discussioncontrasting
confidence: 99%
“…As sulindac sulfide was the most potent compound to bind to Aβ42, we further analyzed this interaction by NMR spectroscopy. We recorded a solution-state two-dimensional 1 H, 15 N correlation spectrum of Aβ42 in the presence and absence of sulindac sulfide (Fig. 3).…”
Section: Analysis Of Gsm-aβ Interaction By Surface Plasmon Resonance mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the lack of a consistent response to GSMs regarding an inversely correlated production of A␤ 42 and A␤ 38 by PS FAD mutants observed earlier argued against a strict precursor-product relationship between A␤ 42 and A␤ 38 (24,25). Moreover, while this manuscript was in preparation, a biophysical study failed to demonstrate GSMbinding to the APP substrate, however, and suggested that the reported GSM-APP interaction (18) was unspecific (26).…”
mentioning
confidence: 76%
“…Certain low potency GSMs such as the NSAIDs flurbiprofen and sulindac sulfide have been reported to bind to the APP CTF as well as to A␤ in the N-terminal third of the APP transmembrane domain (8 -10), although this interaction was questioned by others (11). Another study identified the ␥-secretase subunit PEN-2 as the principal target of non-NSAID-type second generation GSMs (12).…”
mentioning
confidence: 99%